2020
DOI: 10.25182/jgp.2020.15.1.45-52
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro α-Glucosidase Inhibition and Antioxidant Activity of Mulberry (Morus Alba L.) Leaf Ethanolic Extract

Abstract: This present work aimed to investigate the in vitro antioxidant activity and α-glucosidase inhibitory effect of mulberry leaf ethanolic extract. Antioxidant analysis was performed using Thiobarbituric Acid (TBA) assay at concentrations of 125, 200, 500, and 1,000 ppm. The results showed that the optimum incubation time was four days and the extracts could reduce the formation of MDA, i.e. 41.21%, 45.33%, 44.19%, and 36.00%, respectively. This suggests that concentration of 200 ppm was found as the best treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The antioxidant activity of red betel leaf extract compared to the antioxidant activity of noni and Physalis peruviana, ethanol, and n-hexane solvents of red betel leaf was better than noni (Morinda citrifolia L.) extracted with methanol 33 because red betel leaf extract showed no effect prooxidant. Another similar study showed no different results, namely mulberry ethanol extract at a concentration of 200 μg/mL (200 ppm) with an inhibition of 44.19% (Danuri et al, 2020). According to Alfarabi (2010), red betel leaf at a concentration of 200 mg/10 mL with water as a solvent was able to inhibit MDA formation by 81.78%; when compared to this study, 70% ethanol extract and n-hexane extract of red betel leaves had lower antioxidant activity.…”
Section: Discussionmentioning
confidence: 87%
“…The antioxidant activity of red betel leaf extract compared to the antioxidant activity of noni and Physalis peruviana, ethanol, and n-hexane solvents of red betel leaf was better than noni (Morinda citrifolia L.) extracted with methanol 33 because red betel leaf extract showed no effect prooxidant. Another similar study showed no different results, namely mulberry ethanol extract at a concentration of 200 μg/mL (200 ppm) with an inhibition of 44.19% (Danuri et al, 2020). According to Alfarabi (2010), red betel leaf at a concentration of 200 mg/10 mL with water as a solvent was able to inhibit MDA formation by 81.78%; when compared to this study, 70% ethanol extract and n-hexane extract of red betel leaves had lower antioxidant activity.…”
Section: Discussionmentioning
confidence: 87%
“…White mulberry leaf and green apple peel are two natural ingredients, that have shown to reduce postprandial blood glucose levels by regulating the digestion of the carbohydrates and by modulating the uptake of glucose at the brush border of the intestine. The individual capabilities were demonstrated in various randomised clinical studies [11][12][13][14]16,18,19,[21][22][23][24][25][26] . In this randomised, placebocontrolled, crossover study, carried out in healthy normoglycaemic individuals, we have demonstrated the efficacy of a combined extract of white mulberry leaf and green apple peel (Glubloc™) on postprandial glucose and insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry leaf extract not only directly affects α-glucosidase and related enzymes, and influence carbohydrate metabolism and absorption 13,24 . Its ability to moderate insulin spikes is noteworthy, given the direct correlation between elevated systemic insulin levels and increased whole-body glucose uptake 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bitkilerde yaygın olarak bulunan diyet polifenollerinin antioksidan kapasitelerinin yanında, sözü geçen bu sindirim enzimlerine karşı inhibitör etkilerinin de olduğu bildirilmiştir (Xiao vd., 2013;Asgar, 2013). Literatürde farklı tür ve menşeili dut yapraklarının antioksidan ve hipoglisemik etkilerini inceleyen çalışmalar mevcuttur (Anwar vd., 2015;Hasim, Uci ve Didah, 2020;He vd., 2020;Iqbal vd., 2012;Levickiene vd., 2017;Thabti, Marzougui, Elfalleh ve Ferchichi, 2011;Yu vd., 2018). Bu çalışmalar incelendiğinde; dut yapraklarıyla yapılan antioksidan aktivite çalışmalarının toplam fenolik madde ve flavonoid tayinlerinin yanında özellikle DPPH veya ABTS radikallerini giderme aktivitesi ile sınırlı oldukları görülmektedir.…”
Section: Introductionunclassified